Structural insight into small molecule action on Frizzleds - Paweł Kozielewicz (Nature Portfolio, 2020)
WNT-Frizzled (FZD) signaling plays a critical role in embryonic development, tissue homeostasis and human disease but no small molecule drugs targeting FZD with distinct efficacy have emerged so far. Here, authors identify the Smoothened agonist SAG1.3 as a partial agonist for FZD6 with limited subtype selectivity.